Effect of increased pushoff during gait on hip joint forces. Issue 1 (2nd January 2015) - Lewis, Cara L.; Garibay, Erin J.
Abstract Anterior acetabular labral tears and anterior hip pain may result from high anteriorly directed forces from the femur on the acetabulum. While providing more pushoff is known to decrease sagittal plane hip moments, it is unknown if this gait modification also decreases hip joint forces. The purpose of this study was to determine if increasing pushoff decreases hip joint forces. Nine healthy subjects walked on an instrumented force treadmill at 1.25 m/s under two walking conditions. For the natural condition, subjects were instructed to walk as they normally would. For the increased pushoff condition, subjects were instructed to "push more with your foot when you walk". We collected motion data of markers placed on the subjects׳ trunk and lower extremities to capture trunk and leg kinematics and ground reaction force data to determine joint moments. Data were processed in Visual3D to produce the inverse kinematics and model scaling files. In OpenSim, the generic gait model (Gait2392) was scaled to the subject, and hip joint forces were calculated for the femur on the acetabulum after computing the muscle activations necessary to reproduce the experimental data. The instruction to "push more with your foot when you walk" reduced the maximum hip flexion and extension moment compared to the natural condition. The average reduction in the hip joint forces were 12.5%, 3.2% and 9.6% in the anterior, superior and medial directions respectively and 2.3% for the net resultant force. Increasing pushoff may be an effective gait modification for people with anterior hip pain.